2023
DOI: 10.1186/s40168-023-01550-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome of mealworms (Tenebrio molitor Larvae) show similar responses to polystyrene and corn straw diets

Abstract: Background Some insects can degrade both natural and synthetic plastic polymers, their host and gut microbes play crucial roles in this process. However, there is still a scientific gap in understanding how the insect adapted to the polystyrene (PS) diet from natural feed. In this study, we analyzed diet consumption, gut microbiota responses, and metabolic pathways of Tenebrio molitor larvae exposed to PS and corn straw (CS). Results T. molitor lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…This suggests that the ability of T. molitor to degrade PP can be traced back to its ability to degrade natural lignocellulosic polymers. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that the ability of T. molitor to degrade PP can be traced back to its ability to degrade natural lignocellulosic polymers. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the ability of T. molitor to degrade PP can be traced back to its ability to degrade natural lignocellulosic polymers. 31,32,67 Functional Prediction of the Gut Microbial Communities. Functional prediction by PICRUSt analysis revealed a higher abundance of specific enzymes, i.e., alkane-1-monooxygenase, carboxylesterase, cutinase, and dehydrogenase in PP-fed larvae compared to those fed with WB (control) (Figure 3a−f).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While various strains of fungi (e.g., White Rot Fungi 9 and Phanerochaete chrysosporium 10 ) and bacteria (e.g., Pseudomonas citronellolis and Bacillus flexus 11,12 ) have been identified, most studies have primiarily reported the morphological and physicochemical changes of PVC plastic (e.g., weight loss and molecular weight). Notably, many studies have demonstated the ccapacity of insect gut microbiota to biodegrade plastics, including PS 13,14 , PET 15 , PVC 16,17 . However, little is known about the PVC-degrading genes and enzymes within these degrading strains or microbial communities 18 .…”
Section: Introductionmentioning
confidence: 99%